Facial EMG as an Index of Affective Response to Nicotine - Robinson, Jason D. (Exp Clin Psychopharmacol, 2007)
Negative affect reduction has been postulated to be a key feature of cigarette smoking. In the present study, facial electromyography (EMG), heart rate (HR), and skin conductance (SCR) were used to evaluate the affective significance of acute nicotine administration and overnight withdrawal. Smokers (n=115) attended four 90-min laboratory assessment sessions scheduled approximately three days apart. The four sessions provided a complete crossing of two pre-laboratory deprivation conditions (12-hour deprived vs. nondeprived) with two drug conditions (nicotine vs. placebo nasal spray). During each session, smokers viewed affective slides while facial EMG, HR, and SCR were recorded. Results indicated that for women, nicotine nasal spray resulted in lower corrugator EMG activity during both smoking-deprived and nondeprived sessions, compared to placebo. However, nondeprived women also showed an increase in zygomaticus EMG when given nicotine compared to placebo spray, while smoking-deprived women demonstrated a decrease in the zygomaticus response to nicotine compared to placebo. With men, nicotine also appeared to lower corrugator during deprivation, but not nondeprivation, compared to placebo spray, though the contrast only approached significance. With zygomaticus EMG, nicotine spray decreased men’s zygomaticus responding during nondeprivation but not during deprivation, compared to placebo spray. The HR results reflected the stimulatory properties of the drug rather than nicotine’s affective properties, while SCR was unresponsive to our experimental manipulations. The corrugator EMG results support negative reinforcement models of smoking that postulate that acute nicotine use reduces withdrawal-driven negative affect.